ANALISIS PERKEMBANGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI LAHAN TERBANGUN DI KOTA SEMARANG - Putri Ayu Az Zahra; Reny Yesiana; Pratamaningtyas Anggraini; Intan Muning Harjanti (Jurnal Riptek, 2021)
Development of a city is something that cannot be avoided and will continue to happen dynamically from time to time. Along with the development of various urban activities, where the population as a means of implementation has a direct impact on the increasing demand for land. Semarang City, which is the capital of Central Java Province, is also one of the centers for the growth of trade and services, education and service centers for other activities, which have developed very rapidly. This is what stimulates the flow of urbanization in the city of Semarang with the aim of getting a more decent life which will have an impact on the development of built-up land. The purpose of this study is to identify developments and factors that affect built-up land in the city of Semarang as an effort to monitor and anticipate to prevent unwanted negative impacts in the future. Through secondary data collection and continued with analysis using the Supervised Classification method, the results showed that there was a change in land use into built-up land in Semarang City from 1999-2019 covering an area of 11,403.46 Ha or an increase of 29.36%. Based on the results of the analysis of the level of development of built-up land using the quantitative method, it was found that three sub-districts with the category of very high development of built-up land in Semarang City were Ngaliyan District, Mijen District and Tembalang District. Based on multiple linear regression analysis, the equation Y = 20.453 + 0.007X1 + 38.425X2 - 6.775X3 + 3.170X4 and has an R² of 0.835. This means that the independent variables (independent) namely population (X1), distance to the city center (X2), land value (X3) and public facilities (X4) have an influence of 83.5% on changes in built-up land while the remaining 0.165 or 16.5% influenced by other variables not explained in this study.